Hepatitis B virus infection in pregnant women in Baghdad - Hujaz Ismail (مجله كليه طب الكندي)
Background: Globally, hepatitis B is one of the most common infectious diseases. Estimates indicate that at least 2 billion people have been infected with the hepatitis B virus (HBV), with more than 378 million people being chronic carriers. Those individuals at higher risk for acquiring HBV and transmitting disease like pregnant women should be screened for  hepatitis B surface antigen (HBsAg) to prevent transmission by vaccination and operation. Aim of study: The aim of this study was to determine the prevalence of HBsAg and its associated parameters in pregnant women who referred to antenatal clinic in Baghdad Province.